Analisis Perang Dagang AS-China terhadap Ekspor Sektor Manufaktur Unggulan di Indonesia ke Amerika Serikat Tahun 2003-2023 - Farozak Alamin; Emi Maimunah; Nindya Eka Sobita (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the impact of the U.S.-China trade war on exports from Indonesia’s leading manufacturing sectors to the U.S. market during the period 2003–2023. The study employs a quantitative approach using panel data that combines 11 key manufacturing subsectors and 21 time periods, resulting in a total of 231 observations. The estimation method used is the Random Effects Model (REM), selected based on the results of the Chow test, the Hausman test, and the Lagrange Multiplier test. The independent variables used include trade tariffs (a proxy for trade wars), U.S. GDP, Indonesian inflation, the rupiah exchange rate, the Wholesale Price Index (WPI), export competitiveness (RCA), and Foreign Direct Investment (FDI). The results of the study indicate that trade tariffs have a negative and significant effect, U.S. GDP has a positive and significant effect, inflation has a negative and significant effect, the exchange rate has a positive and significant effect, the IHPB has a positive and significant effect, RCA has a positive and significant effect, and FDI has a positive and significant effect on Indonesia’s manufacturing exports to the United States. Simultaneously, all variables have a significant effect with an F-statistic value of 65.37. The model is able to explain 67.23% of the variation in Indonesia’s manufacturing exports to the United States.